Complete mitochondrial genome of the Bingzhi's stout newt (Pachytriton granulosus Chang, 1933) and its phylogenetic placement. Issue 2 (1st February 2021) - Chen, Jing-Yi; Lin, Long-Hui; Zhong, Jun-Jie; Zhou, Yi-Nan; Ding, Guo-Hua
Abstract: The Bingzhi's stout newt ( Pachytriton granulosus Chang, 1933) is distributed in mountainous areas of Zhejiang, China. The first complete mitochondrial genome (mitogenome) of P. granulosus was determined by next-generation sequencing. The size of the assembled mitogenome for P. granulosus was 16, 293 bp, which included 13 protein coding genes, 22 tRNAs, 2 rRNAs, a non-coding region, and a control region (D-loop). The phylogenetic analysis using Bayesian Inference validated the taxonomic status of P. granulosus, showing the close relationship with the other two species from the genus Pachytriton .